2011
DOI: 10.1002/hed.21821
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound‐guided core‐needle biopsy in the assessment of head and neck lesions: A meta‐analysis and systematic review of the literature

Abstract: This meta-analysis confirms that CNB is an excellent method in the assessment of salivary gland lesions and lymphadenopathies inclusive of malignant lymphoma, but it is not ideal for evaluating thyroid lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
170
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(188 citation statements)
references
References 53 publications
12
170
0
2
Order By: Relevance
“…16 In this regard, besides a potential risk of malignant tumor seeding, benign tumors such as pleomorphic adenomas can have problematic recurrences, which may not even be evident until many years after the initial surgery. Although Novoa et al 19 recently reviewed the safety of USCNB in the work-up of 438 head and neck lesions with 7 years of clinical follow-up and found no evidence of tumor cell seeding, further clinical investigation of tumor recurrence following USCNB is necessary in a large population during a long time course before the safety of USCNB can be verified and widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…16 In this regard, besides a potential risk of malignant tumor seeding, benign tumors such as pleomorphic adenomas can have problematic recurrences, which may not even be evident until many years after the initial surgery. Although Novoa et al 19 recently reviewed the safety of USCNB in the work-up of 438 head and neck lesions with 7 years of clinical follow-up and found no evidence of tumor cell seeding, further clinical investigation of tumor recurrence following USCNB is necessary in a large population during a long time course before the safety of USCNB can be verified and widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Novoa et al carried out a meta-analysis of the use of ultrasound-guided core biopsy in head and neck malignancies [68]. The sensitivity for the detection of malignancy in the thyroid was 68%, but a subgroup analysis of thyroid lymphoma was not performed.…”
Section: Core Biopsymentioning
confidence: 99%
“…All patients were diagnosed based on histologic examination of thyroid tissue specimens. Some researchers have suggested that fine-needle biopsy and core-needle biopsy with flow cytometry are useful and less invasive techniques (5,23). However, the more limited specimen obtained by core biopsy than by surgical excision biopsy is usually not representative of the entire tumor, particularly in the case of coexisting MALT and DLBCL histologies.…”
Section: Discussionmentioning
confidence: 99%